Economic and financial consequences of war in Ukraine: Analysis of development scenarios - Marianna Bida; Iryna Ruda (Financial Internet Quarterly, 2022)
The war affects the socio-economic state of Ukraine and is the cause of the deterioration of the economic situation of neighboring countries. Under such conditions, there is a need to carry out assessments of economic losses from the conduct of military operations and forecast the main economic indicators for the nearest period, taking into account the impact of the war. The purpose of the study is to calculate the losses to the economy, the destruction of residential facilities and critical infrastructure facilities in the first 100 days of the war, the assessment of the potential volume of the fall in GDP and the calculation of projected fiscal losses. The calculation of GDP reduction was based on the forecasts of the International Monetary Fund, the World Bank Group and the Government of Ukraine. The expected amount of GDP reduction is calculated using the GAP-analysis method, based on the forecasts made by these institutions in the prewar period, and the calculation of the level of GDP during the war. .
Keywords: 53; 27; 56; 330; potential economic losses from war; real losses; contraction of GDP; fall in GDP volumes